A multiple objective approach for joint ordering and pricing planning problem with stochastic lead times - Zeinab Hosseini; Reza Ghasemy Yaghin; Maryam Esmaeili (Journal of Industrial Engineering International, 2013)
The integration of marketing and demand with logistics and inventories (supply side of companies) may cause multiple improvements; it can revolutionize the management of the revenue of rental companies, hotels, and airlines. In this paper, we develop a multi-objective pricing-inventory model for a retailer. Maximizing the retailer's profit and the service level are the objectives, and shortage is allowed. We present the model under stochastic lead time with uniform and exponential distributions. Since pricing is important and influences demand, the demand is considered as a general function of price. The multiple-objective optimization model is solved using the weighting method as well as the L-P metric method. Concerning the properties of a nonlinear model, a genetic algorithm is taken into account to find the optimal solutions for the selling price, lot size, and reorder point. Finally, numerical examples with sensitivity analysis regarding key parameters are provided.
Keywords: 650; Multi-objective nonlinear optimization; Pricing; Stochastic lead time; L-P metric method; Genetic algorithm